A numerical study of the effects of the longitudinal baffle on nickel ore slurry sloshing in a prismatic cargo hold. (March 2016) - Zhang, Jianwei; Wu, Wanqing; Hu, Junquan
Abstract: The nickel ore slurry sloshing in a rolling partially loaded prismatic cargo hold with a longitudinal baffle is investigated. A numerical model based on the volume of fluid (VOF) method and the non-Newtonian Herschel-Bulkley and Bingham equations is proposed to study the dynamic behavior of nickel ore slurry sloshing. The numerical model is solved by using the finite volume approximations and the dynamic mesh technique is utilized to handle the cargo hold's motion. After taking grid and time step independence study, the numerical results are compared with experimental data. Comparisons show good agreement in the cases investigated. Further, the relationship between the moment amplitude induced on the hold boundary and the excitation frequency is checked numerically. The ratio of baffle height to the initial cargo depth has been changed in the range of 0.0 ≤  h B / d  ≤ 1.2. The variation of the sloshing-induced moment and the deformation of the free surface under different baffle heights have been obtained and discussed. To clearly understand the sloshing behavior of nickel ore slurry, the sloshing of liquid water has also been carried out. Meanwhile, the dynamic viscosity of the nickel ore slurry is monitored. The critical baffle height with regard to the sloshing-induced moment and the elevation difference of the free surface at two sides of the cargo hold has also been presented and discussed. Highlights: We studied the sloshing problem of nickel ore slurry. We investigated the blockage effect of a baffle when considering sloshing problem of nickel ore slurry. As the baffle height increases, the value of the sloshing-induced moment and the free surface elevation keeps decreasing. It has a critical baffle height with regarding to the sloshing-induced moment and the free surface elevation. The changing viscosity of nickel ore slurry was obtained and discussed.